SISTEM PENGARSIPAN ARSIP ELEKTRONIK - Tajrid Salmin (Jurnal Pustaka Ilmiah, 2019)
In the current modern era, manual filing systems are less popular because they are less practical so it is necessary to implement in the form of paperless office or digitalization. The advantages of electronic files are easily visible. There will always be a need for hard-copy printed material, if only to ‘feel’ holding a physical copy of a journal, but despite the possible losses caused by technological changes there are good reasons (including space, searching, access and permanence) to consider the electronic version to be more flexible and useful products.Documents or archives in the form of paper that are stored in offices or government institutions should be managed properly so that they benefit the organization. To keep it easier and safer, some actions are taken, including by melting, sorting, indexing, placing it into a folder and putting it into a filing cabinet. This applies also to electronic archives, which require several methods to manage them so that they are easy to understand and easy to find if needed so that they are useful both when needed or in the future.Keywords: Archives, filing systems, electronic archives.